PENGARUH JUMLAH PENDUDUK, DANA PERIMBANGAN DAN INVESTASI PADA KESEJAHTERAAN MASYARAKAT MELALUI BELANJA LANGSUNG PADA KABUPATEN/KOTA DI PROVINSI BALI TAHUN 2007-2012 - Putu Suciati, Desak Ayu; Sri Budhi, Made Kembar; Jayastra, Ketut (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
The Influence of Population Number, Fund Balance and Investment to People Welfare through Direct Expenses. This study aims is analyzing the influence of the population number, the fund balance and investment directly and indirectly to the community welfare (HDI) through direct expenditure in the regencies/administrative town in Bali Province in the Year of 2007-2012. This research used secondary panel data obtained from the Finance Bureau of the Bali Provincial Secretariat, Board of Investment and Licensing strip of Bali Province, BPS Bali Province and were collected by the method of non-participant observation and interviews. The data were then analyzed using descriptive and quantitative analysis with path analysis (path analysis) and with SPSS 21. The analysis result shows: 1) the number of population has no significant influence on the community welfare, but the fund balance and investment positively influence the community welfare, 2) there is a positive influence indirectly between population number, fund balance and investment to the community welfare (IPM) through direct expenses in the regencies / administrative town in Bali province in 2007-2012.   Keywords: Population number, fund balance, investment, direct expenses and welfare (HDI)
Keywords: Population number, fund balance, investment, direct expenses and welfare (HDI)